Empyema thoracic in a neonate co-infected with SARS-CoV-2 and staphylococcus arouse successfully treated with fibrinolysis: a brief report - Fatemeh Sabzevari; Reza Sinaei; Aazam Gholami; Farzad Tahmasbi (BMC, 2023)
Abstract Background Empyema as a rare cause of respiratory distress in neonatal period has not yet been reported after Corona virus disease 2019 (COVID-19) and even rarely in the context of bacterial infections is age group. Case Presentation The first neonate of quadruplets, resulting from Cesarean-Section of a 30-year-old mother without a history of previous illness, born at 34 weeks of gestation with a birth weight of 1600 gram. All four newborns were hospitalized; while the first one underwent nasal continuous positive airway pressure (N-CPAP) with a positive end-expiratory pressure of 6 and fractional inspired oxygen of 0.6, due to respiratory distress, noting a respiratory score of five out of 12.She was resuscitated one hour later due to bradycardia and underwent ventilator support. She received a single dose of pulmonary surfactant, intravenous paracetamol, and phenobarbital due to respiratory distress syndrome, Pectus Ductus Arteriosus, and unilateral clonic movements, respectively. In the lack of positive blood culture, she extubated two days later and breast-feeding was started. On day eight, she underwent high flow nasal cannula. On day 12, she suddenly developed respiratory distress, mottling, and abdominal distension, leading to N-CPAP and re-evaluation. The nasopharyngeal sampling for severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) real time Polymerase chain reaction and the blood culture for staphylococcus aurous became positive. A large volume pleural effusion including septa and loculation in right hemi-thorax on chest computerized tomography scan and ultrasound was seen, necessitating to thoracotomy, which was not possible due to her general condition. Remdesivir was started and antibiotics changed to a more broad-spectrum coverage. Chest tube was inserted and Alteplase was injected for three consecutive days with beneficial effects. She had no problem for six-month follow up. Conclusion This was a case of empyema thoracic in the context of SARS-CoV-2 and Staphylococcus arouses co-infection. In our experience, it can be treated by chest drainage and fibrinolysis in neonatal period.